Application In Activity Based Costing (ABC) Calculation of Home Development Cost - Hendra Dwi Prasetyo; Kusuma Adi Rahardjo; Iman Supriadi; Nindya Kartika Kusmayati; Moh Wahib (Yayasan Ilomata, 2020)
Activity based costing (ABC) is an improved system of the traditional one. This system is calculating costs that provide accuracy and relevance in allocating overhead costs. This system has an overall cost tracking compared to traditional systems. This research uses a descriptive method of case study approach, which can describe the existence of a variable, symptom or condition. Using this method adjusts the ability to answer the problem under study and hopes to be able to provide clear results and answers. The results of the calculation of housing construction cost using the ABC system on housing in Sidoarjo are able to describe results more accurately and do not cause distortion of costs.